Kajian Pengembangan Ekowisata Salang Pangeran Di Kawasan Taman Nasional Gunung Leuser - Syamsul Arifin; Budi Utomo (Jurnal Serambi Engineering, 2018)
Development of ecotourism is one way to preserve the forest and also for the welfare of the surrounding community. Salang Pangeran ecotourism in Timbang Lawan village is part of the buffer of Gunung Leuser National Park. Since 2014, people of Timbang Lawan village have opened the Salang Pangeran ecotourism for public. Tourists who visit the ecotourism increase significantly. The purpose of this study is to determine the value of potential objects and natural attractions, internal and external factors that affect the development of Salang Pangeran ecotourism and its development strategies. Methods of data collection by conducting literature studies, field observations, interviews with communities and stakeholders and conducting Focus Group Discussions (FGDs). Data analysis on the potential of Objects and Natural Tourist Attraction (ODTWA) described descriptively and it processed by using Guidance Analysis of the Operational Area-Objects and Natural Tourist Attraction (ADO-ODTWA) and SWOT analysis to formulate strategic alternatives. The results of ODTWA analysis in the Salang Pangeran ecotourism area for each criterias are known for attractiveness value is 1260 points (high), accessibility, 725 points (medium), condition of socio-economic environment, 425 points (medium), accommodation, 180 points (high), insfrastructure and supporting facilities, 300 points (high) and availability of clean water, 900 points (high). There are 9 alternative strategies for the Salang Pangeran ecotourism development plan